Breakdown in Pakistan : How Aid is Eroding Institutions for Collective Action - Bano, Masooda, 1973- (Delhi Foundation Books, 2013)
Thirty percent of foreign development aid is channeled through NGOs or community-based organizations to improve service delivery to the poor, build social capital, and establish democracy in developing nations. However, growing evidence suggests that aid often erodes, rather than promotes, cooperation within developing nations. This book presents a rare, micro level account of the complex decision-making processes that bring individuals together to form collective-action platforms. It then examines why aid often breaks down the very institutions for collective action that it aims to promote.
Include Index and Bibliography
Keywords: Non-governmental organizations -- Pakistan -- Associations, institutions, etc